The 2024 NIA-AA biological definition of Alzheimer’s disease: linking biomarkers to clinical practice - Kobayashi, Goh; Hirata, Kosei; Ono, Maiko; Kasuga, Kensaku; Takado, Yuhei (Frontiers in Dementia, 2026)
The 2024 National Institute on Aging–Alzheimer’s Association (NIA-AA) criteria establish a biological definition of Alzheimer’s disease (AD), marking a pivotal step toward linking research biomarkers with clinical practice. This review traces the evolution of AD diagnostic frameworks from the 1984 NINCDS-ADRDA clinical criteria, through biomarker-informed updates in 2011, to the 2024 biology-based criteria that bridge research and clinical care. The 2024 framework defines AD by its underlying pathology rather than clinical symptoms, recognizing that biomarker evidence alone can establish diagnosis. It expands the traditional AT (N) model into a multimodal profile (AT1T2NISV), in which Core-1 biomarkers (A and T1) are diagnostic, while Core-2 biomarkers (T2) support biological staging. Non-specific but mechanistically important processes (N, neurodegeneration; I, inflammation) and common co-pathologies (S, α-synuclein; V, vascular injury) are also incorporated to better capture the complexity of late-life dementia. Recent advances in plasma and PET biomarkers, including p-tau217, mid-region p-tau, and α-synuclein imaging, are redefining biological diagnosis and expanding its reach. Moreover, co-pathologies involving TDP-43, glial dysfunction, and vascular factors contribute to disease heterogeneity and variable therapeutic response. While the 2024 criteria represent a major conceptual step forward, they should be regarded as a dynamic framework open to future integration of emerging biomarkers. Bridging molecular pathology, neuroimaging, and clinical presentation will be essential to realize the goal of patient-centered precision medicine in AD. In this review, we synthesize recent advances in biomarker-based frameworks for AD and discuss co-pathologies, resilience-related modifiers, and emerging evidence challenging traditional interpretations of structural neurodegeneration markers. We also address implications for clinical implementation, including PET standardization and disease-modifying therapies.